Prediction of H2S and HCl formation during RDF and co-gasification in fluidized bed - Gulyurtlu, Ibrahim (2009)
Most solid fuels contain S and Cl and during their gasification, the formation of pollutants such as H2S and HCl becomes inevitable, however, a better understanding of the mechanism involved in their formation and subsequent destruction during the process could help to define operating conditions and to achieve synergy during co-gasification to minimize their emissions. The formation of these pollutants along with the partitioning of S and Cl in the gas and solid phases can be predicted using theoretical models in software packages like FactSage. If the tendency of H2S and HCl emissions predicted by the model corresponds to what has been observed, then an overall mechanism could be derived at using the thermochemical stability data. In this paper a comparison between numerical and experimental results is presented. The results obtained seem to suggest a relationship between the levels of sulphur in the fuels and the concentration of H2S in the gas phase, although the presence of K, Na and Ca may minimize the release of H2S. The formation of HCl seemed to be greatly affected by the inorganic matter of the fuels.